Evaluation of toxicity, mutagenicity, metabolism and formation of 2-dodecylcyclobutanone in irradiated ground beef - Gadgil, Priyadarshini (Kansas State University, 2006)
The effect of fat level and antioxidant Origanox on the formation of 2-dodecylcylobutanone (2-DCB) was investigated in fresh irradiated ground beef patties. Patties containing 15% and 25% fat were irradiated by electron beam at 1, 2, 3, and 4.5 kGy. Ground beef patties with 0.08% Origanox were gamma irradiated at 3.0 kGy. Commercially available irradiated ground beef with different fat levels was analyzed in order to estimate dose absorbed by these samples. The 2-DCB was extracted by Supercritical fluid extraction (SFE) and analyzed by gas chromatography-mass spectrometry (GC-MS). The concentration of 2-DCB increased linearly with dose with no significant difference in 2-DCB concentrations between the two fat levels. The estimated doses applied to the commercial samples ranged between 1.38 kGy and 1.55 kGy. Origanox did not affect the concentration of 2-DCB. Mutagenicity of 2-DCB was evaluated by the Ames assay using five standard Salmonella tester strains with S9 enzyme activation. The Ames assay did not show a mutagenic effect of 2-DCB, including samples incubated with S9. Acute toxicity of 2-DCB was evaluated by the Microtox acute toxicity system and compared with cyclohexanone and 2-nonenal (both GRAS additives). The toxicity of 2-DCB was between that of cyclohexanone and 2-nonenal while the maximum toxic effect elicited by 2-DCB was the least of the three compounds. Metabolism of 2-DCB was investigated in Female Sprague-Dawley rats. Hexane extracts of feces and fat were analyzed by GC-MS. Urine with and without added β-glucuronidase, was monitored for glucuronide complexes by hexane extraction GC-MS. The total amount of 2-DCB recovered in feces was 1.78 ± 0.63 mg over five days, about 3-11% of the total 2-DCB administered. The total amount recovered in fat was 0.08 ± 0.01 mg which was approximately 0.33% of the total 2-DCB administered. No metabolites were recovered in any of the urine extracts.
Keywords: alkylcyclobutanones; 2-dodecylcyclobutanone; toxicity; metabolism; irradiation; mass spectrometry; Agriculture, Food Science and Technology (0359)